Family First or Business First? Balancing Family and Business Interests in an Islamic Economic Perspective - Suud Sarim Karimullah (Institut Agama Islam Sumatera Barat, 2024)
This article aims to prove that Islamic economics can provide holistic solutions that can be applied to achieve a harmonious balance between family and business interests without sacrificing either of them. This study uses a library research method with an integrative and comprehensive literature analysis to develop a solid and applicable theoretical framework. The results state that the balance between family and business in a family business is not just an effort to divide time and roles but a strategic integration that demands a harmonized vision, high professionalism, and strong values of togetherness. Family businesses can develop professionally without sacrificing family ties by building a vision based on Islamic principles, implementing good corporate governance, maintaining open communication, and enforcing strict role boundaries. This strategy makes the family business a space that creates profit and realizes blessings and long-term prosperity. Only with a thorough commitment to these values can a family business become an example of true strength rooted in togetherness and integrity amidst increasingly fierce competition.